2019
DOI: 10.1038/s41389-019-0123-5
|View full text |Cite
|
Sign up to set email alerts
|

Cell division cycle associated 5 promotes colorectal cancer progression by activating the ERK signaling pathway

Abstract: Cell division cycle associated 5 (CDCA5) is implicated in the development and progression of a variety of human cancers. Functional significance of CDCA5 in colorectal cancer (CRC), however, has not been investigated. Using a combination of on-line data mining, biochemistry, and molecular biology, we examined the potential oncogenic activity of CDCA5 and the underlying mechanisms. Experiments with human tissue sample showed increased CDCA5 expression in CRC vs. in noncancerous adjacent tissue, and association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
7
35
0
Order By: Relevance
“…CDCA5 was overexpressed in various tumors, studies have shown that high expression of CDCA5 in CRC may play an essential role in the progression of CRC by activating the ERK signaling pathway and may lead to poor prognosis. 52 Similar results have been found in patients with lung cancer. 53 CDCA5 was transcribed by E2F1 in hepatocytes, promotes tumorigenesis by enhancing cell proliferation and inhibiting apoptosis of hepatocellular carcinoma through the AKT pathway, and was significantly related to the poor prognosis of liver cancer patients.…”
Section: Discussionsupporting
confidence: 75%
“…CDCA5 was overexpressed in various tumors, studies have shown that high expression of CDCA5 in CRC may play an essential role in the progression of CRC by activating the ERK signaling pathway and may lead to poor prognosis. 52 Similar results have been found in patients with lung cancer. 53 CDCA5 was transcribed by E2F1 in hepatocytes, promotes tumorigenesis by enhancing cell proliferation and inhibiting apoptosis of hepatocellular carcinoma through the AKT pathway, and was significantly related to the poor prognosis of liver cancer patients.…”
Section: Discussionsupporting
confidence: 75%
“…However, the role of CDCA5 has been confirmed in other cancers including hepatocellular cancer [30], breast cancer [31], gastric cancer [32], and colorectal cancer [33]. Accumulating studies showed that increased CDCA5 level was a diagnostic biomarker and risk factor for numerous cancers which could enhance the tumor cells' capability of proliferation and metastasis by oncogenic ERK5-AP-1 pathway [33,34]. LMNB1 (also termed as lamin B1) is the vital component of nuclear structure which locates between inner nuclear membrane and peripheral heterochromatin [35].…”
Section: Discussionmentioning
confidence: 99%
“…Spindle pole body component 25 homolog (SPC25), a component of the NDC80 kinetochore complex, plays a crucial role in regulating mitotic chromosome segregation in prostate cancer (Liu et al, 2018). Cell division cycle-associated 5 (CDCA5) serves an important role in promoting colorectal cancer progression by activating the ERK signaling pathway (Shen et al, 2019). Additionally, CDCA5 could be associated with HCC (Tian et al, 2018), breast cancer (Phan et al, 2018), and lung carcinogenesis (Nguyen et al, 2010).…”
Section: Identification Of Targeted Genes In Hcc 773mentioning
confidence: 99%